1997
DOI: 10.1144/gsl.sp.1997.126.01.25
|View full text |Cite
|
Sign up to set email alerts
|

Gravity anomalies and deep structural controls at the Sabah-Palawan margin, South China Sea

Abstract: The hydrocarbon-rich southeastern margin of the South China Sea is divided by NW-SE lineaments into a series of sharply contrasting segments distinguished by, among other things, abrupt changes in gravity patterns. The Sabah segment is bounded to the SW by the Tinjar or West Baram line and to the NE by the Balabac line at the southwest margin of the Sulu Sea. The most prominent gravitational feature of this segment is the strong freeair gravity low associated with the Sabah Trough which lies about 150 km offsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The shallow level of the Moho of about 22 km or even less implies that the crust is likely to have been already thin before subduction/collision took place as suggested by Milsom et al (1997). However, especially the gravity data require an additional thinning from beneath the Dangerous Grounds to beneath the Compressed Thrust Zone (Fig.…”
Section: The Deep Crust and The Mohomentioning
confidence: 88%
See 1 more Smart Citation
“…The shallow level of the Moho of about 22 km or even less implies that the crust is likely to have been already thin before subduction/collision took place as suggested by Milsom et al (1997). However, especially the gravity data require an additional thinning from beneath the Dangerous Grounds to beneath the Compressed Thrust Zone (Fig.…”
Section: The Deep Crust and The Mohomentioning
confidence: 88%
“…Moreover, Hinz et al (1989) suggested that the NW Borneo Trough is not underlain by a southward subducting oceanic crust but that the lower plate is comprised of continental crust similar in structural style to that of the Dangerous Grounds continental terrane. Under the assumption that the NW Borneo Trough is not a subduction trench, it may thus be either interpreted as a sediment-starved foreland trough (Hazebroek and Tan, 1993;Milsom et al, 1997) downfaulted by thrust front loading of the Dangerous Grounds continental terrane or as an asymmetric sedimentary sag basin that developed by uniform-sense simple shearing on the proto-South China Sea continental margin (Schlu¨ter et al, 1996).…”
Section: The Nw Borneo Trough and The Deepwater Thrust Beltmentioning
confidence: 99%
“…The principal features of the geological evolution of northern Borneo are summarized in Hinz et al (1989), Hutchison (1996aHutchison ( , 1996b, Milsom et al (1997), Petronas (1999), Hutchison et al (2000), Hall and Wilson (2000), Morley et al (2003), Morley andHall et al (2008). Northern and Central Borneo were built from the Mesozoic to Holocene, and they record a complex plate tectonic history involving oceanic and continental crust.…”
Section: Geological Frameworkmentioning
confidence: 99%
“…Following complete subduction of the proto-South China Sea oceanic crust, continental crust of the Dangerous Grounds region was partially subducted beneath the Crocker Formation basin of NW Borneo in the latest early Miocene before its buoyancy locked the system (James, 1984;Levell, 1987;Hazebroek and Tan, 1993;Hutchison, 1996aHutchison, , 1996bSandal, 1996;Hall, 1996;Milsom et al, 1997). Subsequently, northern Borneo experienced signifi cant compressional deformation, as documented onshore in folded sedimentary units of late early Miocene to middle Miocene ages (e.g., Sandal, 1996;Morley et al, 2003;Back et al, 2001Back et al, , 2005Back et al, , 2008, as well as offshore in folded and thrusted middle Miocene to present-day shelf and slope sequences (e.g., Levell, 1987;Hinz et al, 1989;Hazebroek and Tan, 1993;Morley et al, 2003;Ingram et al, 2004).…”
Section: Geological Frameworkmentioning
confidence: 99%
“…With the ongoing spreading of the South China Sea, an older region of oceanic crust, the Proto-South China Sea (Hinz et al, 1989;Hall, 1996;Morley, 2002;Hall et al, 2008) was subducted beneath NW Borneo. In Early Miocene times, the continental crust of the Dangerous Grounds entered the subduction zone, before its buoyancy locked the system in the latest Early Miocene (James, 1984;Levell, 1987;Hinz et al, 1989;Hazebroek and Tan, 1993;Hutchison, 1996a, b;Sandal, 1996;Hall, 1996;Milsom et al, 1997). This collision history is reflected in significant compressional deformation documented onshore northern Borneo in folded sedimentary units of late Early Miocene age (e.g.…”
Section: Geological Backgroundmentioning
confidence: 99%